Peningkatan Nilai Perusahaan Berbasis Theory of Firm dan Agency Theory - Wahyu Setiawan (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2022)
Abstract The optimization of shareholder wealth based on the theory of firm and agency theory through investment, funding and dividend decisions has various empirical supports. This model is interesting to be examined in Indonesian companies. The study aims to examine the model for the case in Indonesia with a sample of 18 companies listed on IDX which are members of the LQ-45 index for the 2016-2019 period which were selected by purposive sampling. The research applied panel data regression analysis using the eviews-9 program to answer its objectives. The results show that investment decisions have a significant positive effect, funding decisions have a significant negative effect and dividend decisions have an insignificant negative effect on firm value.